Project Management Information Systems and Project Performance: A Case of NWSC- Kabale. - Abigaba, Jackson (Kabale University, 2023)
This study examined the effect of project management information systems on project performance in Uganda, a case of National Water and Sewerage Corporation, Kabale Branch. This study was based on three objectives namely: the effect PMIS software on the performance of NWSC- Kabale projects; to assess the quality of information generated by PMIS and performance of NWSC- Kabale projects; to investigate the challenges of Project Management Information System towards user satisfaction and performance of NWSC- Kabale projects, and to examine the contributions of Project Management Frequency tables were employed to describe the data since descriptive analysis required presentation of a single variable and its characteristics. A Pearson correlation matrix was used to determine the correlations between the predictor factors and the dependent variable at the bivariate level. To fit the data, linear regression models were employed. According to research results from the regression models, the project performance at NWSC Kabale projects, is positively impacted by PMIS where PMIS software on the performance of NWSC- Kabale projects( R=0.971), challenges of Project Management Information System on project performance with ( R =662) and Contributions of Project Management Information System, on project performance (R=656) .The fundamental finding of this study was that, to the bigger extent, PMIS affects project performance at NWSC Kabale-Projects Therefore, this study recommends that, PMIS should be concentrated on if the NWSC Kabale- Projects are perform well.